Coastal Regions of Papua Students and Teachers’ Responses of Educational Challenges in Generative AI Era: A Case Study - Butarbutar, Ranta (Digital Technologies Research and Applications, 2025)
This study investigates the integration of generative AI in the education system of Papua’s coastal regions, highlighting both opportunities and challenges. Papua’s remote and isolated geography has led to limited access to quality education because of infrastructure and teacher shortages. AI presents transformative potential to address these challenges by improving educational quality, accessibility, and resource availability. This study investigates how AI tools can improve students’ personalized learning, critical thinking, and independence while also supporting teachers with AI-assisted content development. Through qualitative methods, such as interviews and focus groups with university students and teachers, this study examines perceptions of AI’s role in overcoming geographical, technological, and cultural barriers. The research identifies practical benefits, including AI-powered language tools, virtual labs for STEM education, and climate change simulation tools, as well as challenges, such as ethical considerations, digital infrastructure limitations, and the need for region-specific curricula. This study suggests three key strategies for future education: sustainable teacher professional development, curriculum localization, and AI integration into the local content. These initiatives ensure educational relevance, and foster innovation in culturally and ecologically unique environments. This research also calls for further exploration of rural inland areas and policy development.